Estrutura organizacional do fitoplâncton nos sistemas lóticos e lênticos da bacia do Tietê-Jacaré (UGRHi-Tietê-Jacaré) em relação à qualidade da água e estado trófico - Luzia, Anna Paula (2009)
The aim of this work was to study the phytoplankton structure of lentic and lotic systems of Tietê/Jacaré basin located in São Paulo State and the relationship between the composition and dominance of phytoplankton organisms with the water quality and trophic state of the rivers and lakes of this basin. The Tietê/Jacare basin is composed by three main rivers: middle Tietê, Jacaré Guaçu and Jacaré Pepira rivers with their sub basins: Jacaré Guaçu, Jacaré Pepira, middle river Tietê, Bauru and Jau river sub basin. Two lentic systems located in the middle Tietê are Bariri (UHE Alvaro de Souza Lima) and Ibitinga reservoirs, and Broa reservoir (UHE Carlos Botelho) in Jacare Guaçu sub basin. The limnological variables which are responsible by the water quality and its trophic state index were analysed in the two periods of the year dry and wet seasons. They were measured pH, temperature, dissolved oxygen, oxide-reduction potential, total dissolved solids, electric conductivity, alkalinity, hardness, water transparency, total particulate phosphorous, total dissolved phosphate, total inorganic phosphate, silicate, total suspended solids, total nitrogen, ionic components (fluoride, chloride, nitrite, bromide, nitrate, sulfate, ammonium, potassium, magnesium and calcium), dissolved and particulate organic carbon, dissolved inorganic carbon, chlorophyll a. Regarding phytoplankton community, the identification was made at the genus level, and the richness, diversity index equitability and dominance were analyzed to establish the relation between trophic state and the dominance of different phytoplankton classes as well as the richness and diversity of organisms both in lentic and in lotic ecosystems. Also short term variation of physical and chemical variables promoted by the cold fronts was studied in the Bariri reservoir to verify the occurrence of thermal stratification and destraification that affect the composition structure of phytoplankton and its spatial distribution.